Pengembangan Sikap Keberagamaan Peserta Didik Era 4.0 - Majdudin Nurul Huda (Sekolah Tinggi Ilmu Tarbiyah Tihamah, 2023)
In the last decade, the world of education in Indonesia has faced major challenges regarding student safety in schools. The challenge in question is a crisis of student morality or character which is marked by the increasing phenomenon of violence in schools or what is generally known as bullying. This case of bullying occurs because they can show their true identity which might be considered something